An overview of inflammatory breast cancer - Siddiqui, Mohammad; Alsarhan, Mustafa; Almutairi, Faisal; Salman, Ahmed; Alroudan, Dhari; Alotaibi, Saleem; Alomran, Abdullah; Awaji, Taghreed; Buarish, Sadaf; Aldahlawi, Raghad; Wali, Nizar; Siddiqui, Malaz (International Journal Of Community Medicine And Public Health, 2022)
Inflammatory breast cancer is an uncommon and severe malignancy that frequently goes undiagnosed at first because it presents similarly to more benign breast diseases like mastitis, resulting in delayed treatment. Inflammatory breast cancer affects 1% to 5% of all occurrences of breast cancer and accounts for 8% to 10% of all breast cancer-related deaths. Erythema, skin abnormalities, nipple inversion, edema, and warmth of the affected breast are all signs of inflammatory breast cancer. Recognized risk factors for inflammatory breast cancer include young age at the time of diagnosis, obesity and African American ethnicity. Rapid onset within 3 months and pathologic evidence of invasive carcinoma leads to diagnosis of disease further including erythema occupying at least one-third of the breast, tumour may or may not be present in this case. Chemotherapy, surgery, and radiation make up the trimodal therapy used to treat inflammatory breast cancer. A modified radical mastectomy performed as part of an aggressive surgical strategy improves survival rates. Although patients with inflammatory breast cancer have worse outcomes than those with noninflammatory breast cancer, those who complete trimodal therapy have a positive locoregional control rate, highlighting the significance of an early diagnosis. Physicians must be aware and examine any clinical manifestation of inflammatory breast cancer if present to make a prompt diagnosis and refer patient for expert care timely also awareness and cancer screening can help in prevention of disease. The purpose of this research is to review the available information about an overview of inflammatory breast cancer.